A New Generation Cooling Device Employing MOF - Ali, Syed Muztuza (2017)
This article presents the thermodynamic framework of a single effect two-bed adsorption chiller employing “ HKUST-1 type metal organic frameworks (MOFs)” as adsorbent and water as adsorbate, which is based on the experimentally validated adsorption isotherms and kinetics data. The experimentally measured MOFs + water based isotherms and kinetics data are fitted with Toth and Langmuir adsorption isotherm models and LDF kinetics equations. Compared with the experimentally measured isotherms and kinetics based numerical performance data of conventional adsorption chiller (RD silica gel + water pair), we found that the new working pair provides better cooling capacity and performances. From numerical simulation, it is found that the cooling capacity can be increased up to 27% of the parent silica gel + water adsorption chiller and the coefficient of performance (COP) can be improved up to 5% at optimum conditions.